2014
DOI: 10.2174/1568026614666140808124638
|View full text |Cite
|
Sign up to set email alerts
|

4(1H)-Pyridone and 4(1H)-Quinolone Derivatives as Antimalarials with Erythrocytic, Exoerythrocytic, and Transmission Blocking Activities

Abstract: Infectious diseases are the second leading cause of deaths in the world with malaria being responsible for approximately the same amount of deaths as cancer in 2012. Despite the success in malaria prevention and control measures decreasing the disease mortality rate by 45% since 2000, the development of single-dose therapeutics with radical cure potential is required to completely eradicate this deadly condition. Targeting multiple stages of the malaria parasite is becoming a primary requirement for new candid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 51 publications
0
22
0
Order By: Relevance
“…Quinolones are used clinically for treatmento ft uberculosis, [17] selected examples have acquired lead status as antimalarial drugs [18,19] and display potent dual target effects when combined with the appropriate drug partner. [19] The precept is that artemisinins and other peroxides behave as oxidants in the intracellularm ilieu by rapidly oxidizingr educed flavin cofactors such as FADH 2 of flavoenzyme disulfide reductases important for maintaining levels of GSH and other endogenoust hiols required for intercepting reactive oxygen species( ROS). [16] Pf as an aerobic organism experiences abnormally high oxidative stress within an erythrocyte.…”
Section: Introductionmentioning
confidence: 99%
“…Quinolones are used clinically for treatmento ft uberculosis, [17] selected examples have acquired lead status as antimalarial drugs [18,19] and display potent dual target effects when combined with the appropriate drug partner. [19] The precept is that artemisinins and other peroxides behave as oxidants in the intracellularm ilieu by rapidly oxidizingr educed flavin cofactors such as FADH 2 of flavoenzyme disulfide reductases important for maintaining levels of GSH and other endogenoust hiols required for intercepting reactive oxygen species( ROS). [16] Pf as an aerobic organism experiences abnormally high oxidative stress within an erythrocyte.…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, we have shown that old, potent drug scaffolds can be optimized into clinical candidates (2). Menoctone represents an interesting case in which there was evidence of efficacy against multiple stages, although much was not known since the drug was abandoned shortly after its discovery.…”
Section: Discussionmentioning
confidence: 99%
“…The increased prevalence of drug-resistant parasites and insecticide-resistant vectors continues to drive the need for new treatments for this disease. New drugs are urgently needed, and in some cases old compounds with proven antimalarial activity can serve as the basis for lead optimization of new potent antimalarial drugs (2). Menoctone, also known as 2-hydroxy-3-(8-cyclohexyloctyl)-1,4-naphthoquinone, was first synthesized by Fieser et al in 1948 (3).…”
mentioning
confidence: 99%
“…6 The third partner is logically constructed about the 4(1H)-quinolone scaffold. In addition to being used clinically against a variety of infectious diseases including tuberculosis, 7 certain quinolones have acquired lead status for development of drugs for treatment of toxoplasmosis 8,9 and malaria 10,11,12 respectively.…”
Section: Graphical Abstractmentioning
confidence: 99%
“…6 The third partner is logically constructed about the 4(1H)-quinolone scaffold. In addition to being used clinically against a variety of infectious diseases including tuberculosis, 7 certain quinolones have acquired lead status for development of drugs for treatment of toxoplasmosis 8,9 and malaria 10,11,12 respectively.Our attention is drawn to decoquinate (DQ, 1) that has been used for many years in veterinary medicine largely coadministered with poultry feed for treatment of coccidiosis wherein it displays negligible toxicity. 13,14 It is also used against other apicomplexan infections in animals 15 and is highly active in a murine model against Toxoplasma gondii.…”
mentioning
confidence: 99%